La evolución, entre ciencia, razón y fe - Juan Luis Lorda (Scientia et Fides, 2015)
Evolution: Between Science, Reason, and Faith Evolution is a topic of interest to science, philosophy and Christian theology. We look for the points of dialogue. We will follow this outline: 1. An introduction where we benefit from two quotes, by Chesterton and Tolstoy, to frame our reflection. Also, we will think about what is required to do real science. 2. We will study what is scientifically proven about evolution and what not. 3. We will discuss the claims that are inspired by science but actually belong to philosophy (or ideology). 4. We will add what can be said from the Christian faith's point of view.